The Initial Phases of the Development of J.‑M. R. Tillard’s Theological Thought - Матић, Златко (Sabornost - The Theological Year-book, 2016)
Rome‑catholic theologian J.‑M. R. Tillard o.p. (1927–2000) was one of the most important ecumenists of the second half of the 20th century. The author offers some key indicators regarding Tillard’s theological topics: Eucharistic theology, the renewal of religious life and communion ecclesiology. Tillard’s ecumenical involvement (after Second Vatican council) has a deep consequence on his forty‑year rich theological work. But, Tillard’s interest in the sacraments and the religious life has a particularly ecclesiological importance, with his focus — the notion of koinonia.